International Financial Reporting Standards Foreign Direct Investment in Asean Countries - Maryam Yousefi Nejad; Azlina Ahmad; Mohd Fairuz Md Salleh; Ruzita Abdul Rahim (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2018)
The objective of this study is to investigate the relationship between International Financial Reporting Standard (IFRS) and Foreign Direct Investment (FDI) inflows. FDI has been identified as an economic consequence of IFRS. However, thus far, few studies have examined this issue in developing countries and there are no studies which have examined IFRS-FDI in ASEAN countries. In order to fulfill this objective, this study hypothesizes that IFRS is positively associated with FDI inflows. The hypothesis was empirically tested using a sample consisting of the ten ASEAN countries from 2001 to 2016, using a bias corrected Least Square Dummy Variable (LSDVC), and Ordinary Least Square (OLS). The results of the LSDVC and OLS analyses indicate that IFRS is positively associated with FDI inflows. Normally after the adoption of a new standard such as IFRS, regulators, practitioners and academicians would be interested in understanding the consequences. Therefore, this study contributes to the understanding of the economic consequences of IFRS. This study also provides evidence regarding the outcomes of IFRS, from the aspects of FDI inflows’ enhancement. Therefore, the outcomes of this study may be useful for adopter and non-adopter countries to understand the economic consequences of IFRS. The findings may also provide important inputs to policy makers of non-adopter countries who are contemplating the adoption of IFRS. The positive relationship between IFRS and FDI inflows provides evidence that IFRS is an important determinant of FDI inflows, and eventually economic growth.